Distribution and spread of tigecycline resistance gene tet(X4) in Escherichia coli from different sources - Fan, Xin-Yan; Jiang, Yue; Wu, Han; Liu, Jie; Gu, Qing-Yun; Wang, Zhen-Yu; Sun, Lin; Jiao, Xinan; Li, Qiuchun; Wang, Jing (Frontiers in Cellular and Infection Microbiology, 2024)
Tigecycline serves as a last-resort antimicrobial agent against severe infections caused by multidrug-resistant bacteria. Tet(X) and its numerous variants encoding flavin-dependent monooxygenase can confer resistance to tigecycline, with tet(X4) being the most prevalent variant. This study aims to investigate the prevalence and characterize tigecycline resistance gene tet(X) in E. coli isolates from various origins in Yangzhou, China, to provide insights into tet(X) dissemination in this region. In 2022, we tested the presence of tet(X) in 618 E. coli isolates collected from diverse sources, including patients, pig-related samples, chicken-related samples, and vegetables in Yangzhou, China. The antimicrobial susceptibility of tet(X)-positive E. coli isolates was conducted using the agar dilution method or the broth microdilution method.Whole genome sequencing was performed on tet(X)-positive strains using Illumina and Oxford Nanopore platforms. Four isolates from pig or pork samples carried tet(X4) and exhibited resistance to multiple antimicrobial agents, including tigecycline. They were classified as ST542, ST10, ST761, and ST48, respectively. The tet(X4) gene was located on IncFIA8-IncHI1/ST17 (n=2), IncFIA18-IncFIB(K)-IncX1 (n=1), and IncX1 (n=1) plasmids, respectively. These tet(X4)-carrying plasmids exhibited high similarity to other tet(X4)-bearing plasmids with the same incompatible types found in diverse sources in China. They shared related genetic environments of tet(X4) associated with ISCR2, as observed in the first identified tet(X4)-bearing plasmid p47EC. In conclusion, although a low prevalence (0.65%) of tet(X) in E. coli strains was observed in this study, the horizontal transfer of tet(X4) among E. coli isolates mediated by pandemic plasmids and the mobile element ISCR2 raises great concerns. Thus, heightened surveillance and immediate action are imperative to curb this clinically significant resistance gene and preserve the efficacy of tigecycline.